2022
DOI: 10.3390/diagnostics12040866
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome of Differentiated Thyroid Cancer Patients—Fifty Years of Croatian Thyroid Disease Referral Centre Experience

Abstract: Background: Indolent nature but a high incidence of differentiated thyroid cancer (DTC) remains a challenge for optimizing patient care. Therefore, prognostic factors present valuable information for determining an adequate clinical approach. Methods: This study assessed prognostic features of 1167 papillary (PTC) and 215 follicular (FTC) thyroid cancer patients that had undergone surgery between 1962 and 2012, and were followed-up up to 50 years in a single institution, till April 2020. Age, gender, tumor siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The incidence of differentiated thyroid cancers (DTC) continues to increase worldwide, almost entirely due to the increasing detection of papillary thyroid cancer (PTC) (Vaccarella et al 2016 ). Most PTC are well differentiated, have relatively sedentary clinical behavior, and have mean 10-year survival rates between 80 and 95% (Sherman 2003 ; Jukic et al 2022 ). Despite the long survival associated with PTC, approximately 20–30% of patients relapse over several decades, with two-thirds of these relapses occurring within the first decade after initial treatment (Brassard et al 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of differentiated thyroid cancers (DTC) continues to increase worldwide, almost entirely due to the increasing detection of papillary thyroid cancer (PTC) (Vaccarella et al 2016 ). Most PTC are well differentiated, have relatively sedentary clinical behavior, and have mean 10-year survival rates between 80 and 95% (Sherman 2003 ; Jukic et al 2022 ). Despite the long survival associated with PTC, approximately 20–30% of patients relapse over several decades, with two-thirds of these relapses occurring within the first decade after initial treatment (Brassard et al 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Significant improvements in the diagnosis and treatment of DTC have provided an excellent prognosis. In general, overall survival rates for TC are high, especially in patients with DTC, with 10-year survival rates ranging from 80 to 95 percent ( 5 , 6 ). However, some studies in recent years have found an increase in mortality among patients with advanced-stage PTC ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…1 Early differentiated thyroid cancer is compatible with long survival, necessitating the need for a prompt diagnosis and proper management. 2 Thyroid nodules are a common entity. Examination of autopsy specimens of those without clinical thyroid disease showed thyroid nodules larger than 1-cm in 50%.…”
Section: Introductionmentioning
confidence: 99%